ANALYSIS OF RECEIVABLE TURNOVER AND DEBT TO EQUITY RATIO ON RETURN ON ASSETS IN LQ45 INDEX ENERGY COMPANIES - Purba, Ayuwinarti; Yusuf, Muhammad; Gurendrawati, Etty (Faculty of Economics and Business, 2025)
This research aims to analyze the effect of receivable turnover and debt to equity ratio (DER) on return on assets (ROA) in energy companies listed in the LQ45 index. The research sample consists of 45 observation data taken from 9 energy companies for 5 years. The analysis method used is multiple linear regression with classical assumption testing to ensure the validity of the model. The results showed that receivable turnover has no significant effect on ROA, while DER has a significant effect on ROA. Simultaneously, both independent variables have a significant effect on ROA, but the largest contribution comes from DER. This finding suggests that the funding structure, specifically the debt-to-equity ratio, plays an important role in determining the profitability of energy companies. This study implies that prudent debt management is necessary to increase profitability and attract investors' interest in the stock market.